PENINGKATAN TRANSAPARANSI KEUANGAN PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) KELURAHAN JOMBLANG, KECAMATAN CANDISARI, SEMARANG MELALUI PEMANFAATAN TEKNOLOGI INFORMASI - Hayu Wikan Kinasih; Melati Oktafiyani; Hermawan Triono; Bambang Minarso; Agung Prajanto (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) are business units that have a major contribution to the economy. Issues that often occur in MSMEs are related to the business sustainability of MSMEs. One of the reasons for this business sustainability is the financial condition of MSMEs. The problem that often occurs in MSMEs is the lack of ability and knowledge of MSME to manage their finances. Similar to what happened to MSMEs in Jomblang Village, Candisari District, MSME rarely recorded their transactions, resulting in loss of control in business activities, which affected business continuity. Community partnership activities carried out at the Jomblang MSMEs aim to increase the knowledge and ability of MSME actors in managing their businesses, especially in terms of finance. The implementation of the activity begins with survey activities, socialization, providing training, and continues with evaluation activities. The implementation of the results of the activities carried out is a web-based financial system application, which is expected to help facilitate MSME in carrying out their financial recording.